Antibacterial and magnetic response of site-specific cobalt incorporated hydroxyapatite - Bhattacharjee, Arjak; Gupta, Anshul; Verma, Madhu; Anand, Murugan Prem; Sengupta, Pradyut; Saravanan, Matheshwaran; Manna, Indranil; Balani, Kantesh (Ceramics international, 2020)
Hydroxyapatite [HA, Ca10(PO4)6(OH)2] based ceramics are a potential candidate for orthopedic implants, bone cements, and bioactive coating over metallic implants due to their compositional similarities [Ca/P = 1.67] with human bone. Cobalt doping in HA can greatly enhance angiogenesis and vascularization along with incorporating antimicrobial properties to HA. For the first time, this work reports the importance of Co doping sites on biological and magnetic properties of HA. In the current work, Co doing in HA has been carried out according to the chemical formula Ca10(PO4)6Cox(OH)2-α and Ca10-x Cox(PO4)6(OH)2, (x = 0, 0.2 and 0.3) to assess the correlation of individual Co incorporation sites on crystal chemistry, cytotoxicity, magnetic properties, ion leaching and antibacterial efficacy. Dependence of antibacterial efficacy on different doping sites revealed that cytocompatible Co doped HA is antibacterial against E. coli, and S. aureus mainly after substitution of Co in Ca site. Additionally, a minor antibacterial effect has been noticed after Co doping in OH channels. Interestingly, the Ca substituted Co doped HA shows Co leaching up to ∼758 ppb (obtained from inductively coupled plasma-mass spectrometry), which comes to only ∼27 ppb after incorporating Co in OH channel. This higher Co leaching (when doped at Ca site in comparison to that at OH channels) is the major cause of better antibacterial efficacy. Vibrating sample magnetometer measurements showed that the order of mr and ms values significantly changes after altering the doping sites, due to change in local Co environment. Thus, this work proves that different doping sites of Co doped HA can greatly enhance its antibacterial properties with significant changes in crystallographic and magnetic properties, which make Co doped HA an ideal choice as a bone replacement material or drug delivery agent with tailored properties depending on the doping sites.